MUTU ORGANOLEPTIK DAN KANDUNGAN HISTAMIN PENYEDAP RASA BUBUK IKAN TUNA SIRIP KUNING (THUNNUS ALBACARES) - Fadila Fadila; Juhartini (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
Flavored yellowfin tuna powder flavoring stimulates the development of North Maluku local food preparations into a seasoning without MSG which in this study was tested directly on processed vegetables with the aim to determine the organoleptic quality. In addition, histamine content and pH levels were tested. This type of research is an experimental study carried out in April - October 2019 in the Laboratory of Food Administration of the Department of Nutrition Health Polytechnic Ministry of Health Ternate and PT. Saraswanti Indo Genetech, Bogor. Organoleptic test results obtained organoleptic quality in vegetable B1 (stir-fried water spinach added yellow fin tuna powder) is preferred with a quality value of 7.0 for appearance and color, and 6.0 for aroma and taste, than for A1 vegetables (vegetable soups that are yellow fin tuna powder was added) with a quality value of 6.0 for appearance and color, and 5.0 for aroma and taste. Different test results between A1 and A2 as well as B1 and B2 obtained a value of p> 0.05 which means no significant difference. The content of histamine flavoring powder yellow fin tuna is 81.44 mg / kg and pH 5.76. It was concluded that yellow fin tuna powder was better added to stir-fried water spinach than vegetable soup and was not significantly different between vegetables added with yellow fin tuna powder and other flavorings (with MSG), and the content of histamine and pH was still relatively safe.